Temperature and Doping Dependencies Junction Of Polythiophene Schottky Barrier - Abbas, S.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The junction between polythiophene, a conducting polymer formed by electrochemical polymerization, and n-type silicon was studied the temperature and doping dependencies were observed in the junction characteristics. The increase of junction temperature leads to increase the saturation current, the barrier height, and decrease of the ideality factor for junction. While the reduction in doping concentration causes a decrease in the forward current. The results were explained according to the conventional Schottky diode theories.